Identifying the Primary Kinetic Factors Influencing the Anterior–Posterior Center of Mass Displacement in Barbell Squats: A Factor Regression Analysis - Diwei Chen; Dong Sun; Fengping Li; Dongxu Wang; Zhanyi Zhou; Zixiang Gao; Yaodong Gu (Sensors)
Background: Barbell squats are commonly used in strength training, but the anterior–posterior displacement of the Center of Mass (COM) may impair joint stability and increase injury risk. This study investigates the key factors influencing COM displacement during different squat modes.; Methods: This study recruited 15 male strength training enthusiasts, who performed 60% of their one-repetition maximum (1RM) in the Front Barbell Squat (FBS), High Bar Back Squat (HBBS), and Low Bar Back Squat (LBBS). Joint moments at both the hip, knee, and ankle were collected using a motion capture system and force plates, and a factor regression analysis was conducted using SPSS.; Results: In the FBS, primary factors influencing COM displacement included right knee adduction–abduction (38.59%), knee flexion–extension (31.08%), and hip internal–external rotation (29.83%). In the HBBS, they were right ankle internal–external rotation (19.13%), hip flexion–extension (−19.07%), and left knee flexion–extension (19.05%). In the LBBS, the key factors were left knee adduction–abduction (27.82%), right ankle internal–external rotation (27.59%), and left ankle internal–external rotation (26.12%).; Conclusion: The study identifies key factors affecting COM displacement across squat modes, with knee flexion–extension being dominant in the FBS and hip moments more significant in the HBBS and LBBS. These findings have implications for optimizing squat training and injury prevention strategies.